Caregivers’ Perspectives on Transitioning Dental Care for Adolescents with Special Healthcare Needs–A Cross-Sectional Study - Glenn Canares; Roxanne Clarke; Erica Caffrey; Sydnee Chavis (International Journal of Dentistry)
Introduction. Few studies have investigated the concerns of caregivers of adolescents with special health-care needs (ASHCN) regarding the barriers and challenges of transitioning from a pediatric to an adult-based dental home. The purpose of this study was to assess these perceptions. Methods. A 23-question survey was administered to guardians of ASHCN who presented to the pediatric dental clinic at the University of Maryland. Question types were either multiple choice, Likert scale responses, or open-ended. A descriptive analysis and Fisher’s exact test were performed. Keywords were evaluated from the open-ended answers. Results. Twenty-seven caregivers completed the survey over a six-month period. Sixty-six percent of caregivers were aware that dental needs change as child ages and thought that transitioning was a logical next step, 78% had concerns about transitional care, and 70% did not have the desire to transition. Fisher’s exact analysis comparing awareness of transition versus the desire to transition was p<0.10. Conclusion. Most caregivers were aware of the changing dental needs of ASHCN and believed transitioning was a logical step. Many caregivers lacked readiness and perceived multiple barriers to transitioning. Awareness of the need to transition from pediatric to adult-based dental homes was not correlated with the readiness to transition.